1998
DOI: 10.1007/bf03011998
|View full text |Cite
|
Sign up to set email alerts
|

Nasotracheal intubation in the presence of frontobasal skull fracture

Abstract: Nasotracheal intubation in the presence of frontobasal skull fracturePurpose: To present a case of maxillofacial trauma and basal skull fracture (BSF) in whom nasotracheal intubation (NTI) was successfully used, without complication, to facilitate surgical fixation. To present alternative methods of airway management in this situation and to review the evidence supporting the notion that NTI is contraindicated in the presence of basal skull fracture.Clinical features: A 17-yr-old man was referred for surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…But there is now enough data to suggest that nasotracheal intubation is not an absolute contraindication in the presence of nasal bone fractures, base of skull fractures and CSF leak [11][12][13]. Rhee K J et al, have shown that complications associated with skull base fractures are not increased when nasotracheal intubations are performed in the field [14].…”
Section: Resultsmentioning
confidence: 99%
“…But there is now enough data to suggest that nasotracheal intubation is not an absolute contraindication in the presence of nasal bone fractures, base of skull fractures and CSF leak [11][12][13]. Rhee K J et al, have shown that complications associated with skull base fractures are not increased when nasotracheal intubations are performed in the field [14].…”
Section: Resultsmentioning
confidence: 99%
“…Nasotracheal intubation is a contraindication in cases of trauma of the skull base (Arrowsmith et al 1998, Marlow et al 1997, Rhee et al 1993) [1,10,12,13] because of possibility of iatrogenic meningitis, difficult intubation and difficulty in performing treatment of fractures of the nasal pyramid at the same time (Smoot et al 1997) [15,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of these modifications are reported in the literature. 1,3,[10][11][12][13][14][15] 3. Though this method is a good option for the securing the airway of patients with multiple fractures in the maxillofacial region, it is not free of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Potential complications of nasotracheal intubation are mucosal dissection, injury to adenoids, meningitis, sepsis, sinusitis, epistaxis, dislodgement of bony fragments, and obstruction of the tube by the distorted airway anatomy or rarely intracranial intubation. 3 In patients requiring simultaneous nasal or nasoorbital ethmoid reconstruction after the rigid fixation of mandible and/or maxilla, intraoperative switching over of the endotracheal tube (ETT) from nasal to oral route is required which may compromise the surgical field sterility and may increase the possibility of pulmonary aspiration. Possible difficulty in airway management, disruption of surgical repair, and obstruction to the operative field are additional limitations.…”
Section: Introductionmentioning
confidence: 99%